PENGARUH TINGKAT PENDIDIKAN ORANG TUA DAN HASIL BELAJAR TERHADAP MINAT SISWA MELANJUTKAN STUDI KE PERGURUAN TINGGI PADA SISWA SMA NEGERI 1 KOTO BARU TAHUN AJARAN 2013/2014 KABUPATEN DHARMASRAYA - Andari, Tri; Tanjung, Mirna; Yolamalinda, Yolamalinda (Pendidikan Ekonomi, 2014)
ABSTRACT Â The aims of this research to know, how far the level of parentâs education and learning outcomes influence toward interest student to continue the study to university. Types of this research is associative. The research location is in SMA Negeri 1 Koto Baru, Dharmasraya. Technique sampling using proportional random sampling to the proportion of 40 % in each class the result of sample of the research is 73 respondent with multiple linear regression analysis. The results of this study indicate that : 1) The level of parentâs education have positive effect on the studentâs interests Â to continue their study at the college studentâs of SMA Negeri 1 Koto Baru academic school yearâs 2013/2014 Dharmasraya. 2) The results of study have positive effect on the students interest to continue their study at the college students of SMA Negeri 1 Koto Baru academic school yearâs 2013/2014 Dharmasraya. 3) The level of parentâs education and learning outcomes are jointly have positive effect on the studentâs interests Â to continue their study at the college students of SMA Negeri 1 Koto Baru academic school yearâs 2013/2014 Dharmasraya.Â